Improving Seismic Performance of Structure with Semi-rigid floor using VSL-Gensui Damper - Pamuda Pudjisuryadi; Andre Halim; Alexander Keith Kandiawan; Benjamin Lumantarna (Institute of Research and Community Outreach - Petra Christian University, 2020)
Deficient structures can be strengthened using various methods, and installing damper devices is one of such methods. In this study, effectiveness of Vorspann System Losinger (VSL) Gensui Damper to improve structural performance of deficient building with semi-rigid floors is investigated. The considered building is subjected to spectrum consistent ground accelerations generated from El Centro 18 May 1940 earthquake N-S and E-W components in accordance to Indonesian Seismic Code (SNI 1726:2012) for Mataram City. Modified Simplified Sequential Search Algorithm (MSSSA) and Optimum Damper Allocation Method (ODAM) methods are used to efficiently placed the dampers on the building until allowable drift limits specified by the code are met. Results show that installation of VSL Gensui Dampers can effectively reduce structural drifts. Further, it should be noted that the placement of dampers must be well distributed among frames in the same story, since their drifts may differ significantly in building with semi-rigid floors.